Design and Implementation of a Laziness Muscle Treatment Device - Ibrahim, Abdullah Ashraf; Mohammed, Mohammed Deyaa; Mohammed, Omar Laith (American Journal of Botany and Bioengineering, 2025)
The project is intended for the measurement of an EMG signal that the device will process and present it. According to the signal, the muscle will be treated using the Bluetooth, (courses, movements in each course, and the speed of movements) will be controlled. sensor will then sense the movement of the arm muscle and measure it’s effectiveness , then pass the signal to the Arduino, which will process the signal, converting it from analog to digital, and send it to the smart device to present it. The doctor will adjust the settings (courses, movements, and speed) according to his diagnosis for the case.